Umbilical cord mesenchymal stem cell-derived secretome as a potential treatment for systemic lupus erythematosus: A double-blind randomized controlled trial - Nurudhin, Arief; Werdiningsih, Yulyani; Sunarso, Indrayana; Marwanta, Sri; Damayani, Aritantri; Prabowo, Nurhasan A.; Affandi, Andri; Gazali, Itqan; Safitri, Ayu SI.; Sidarta, Brigitte RA. (Narra Sains Indonesia, 2025)
Umbilical cord mesenchymal stem cell-derived (UCMSC-derived) secretome is anti-apoptotic, anti-inflammatory, antifibrotic, angiogenic, and tissue-regenerating. Thus, it may treat systemic lupus erythematosus (SLE). The aim of this study was to investigate the impact of the UCMSC-derived secretome on SLE patients' disease activity, using Mexican systemic lupus erythematosus disease activity index (MEX-SLEDAI) score, complement (C3 and C4) levels, tumor necrosis factor-alpha (TNF-α), anti-double-stranded DNA (anti-dsDNA), and interleukin-6 (IL-6) levels. This double-blind randomized controlled trial investigated the efficacy and safety of UCMSC-derived secretome in SLE patients with moderate disease activity. A total of 29 female patients were randomized into two groups to receive weekly 1.5 cc intramuscular injections of UCMSC-derived secretome or placebo (0.9% NaCl) for six weeks. Disease activity was assessed using the MEX-SLEDAI score, C3 and C4 levels, pro-inflammatory cytokines (IL-6 and TNF-α), and anti-dsDNA antibodies at baseline, Day 22, and Day 43. Results showed a significant reduction in MEX-SLEDAI scores in the secretome group compared to the placebo group (p<0.05). Complement C3 levels significantly increased in the secretome group on Day 43, indicating improved immune homeostasis, while C4 levels did not show significant differences between groups. IL-6 and TNF-α levels showed decreasing trends in the secretome group. Anti-dsDNA levels exhibited a decreasing trend in the secretome group, though not statistically significant. Importantly, no severe adverse events were observed, underscoring the safety of the intervention. UCMSC-derived secretome demonstrated immunomodulatory and anti-inflammatory effects, reducing disease activity in SLE patients. These findings suggest its potential as a safe and effective adjunct therapy for SLE, although further studies with larger sample sizes and extended follow-up periods are needed to validate these results.